VEGFR-1 Pseudogene Expression and Regulatory Function in Human Colorectal Cancer Cells - Ye, Xiangcang (Mol Cancer Res, 2015)
A large number of pseudogenes have been found to be transcribed in human cancers. However, only a few pseudogenes are functionally characterized. Here, we identified a transcribed pseudogene of vascular endothelial growth factor receptor-1 (VEGFR1), or fms-related tyrosine kinase 1 (FLT1), in human colorectal cancer (CRC) cells. Interestingly, this pseudogene (designated as FLT1P1) was found to be transcribed bidirectionally and functionally modulated cognate VEGFR1 protein expression in the cells. Mechanistically, expression of FLT1P1 antisense transcript not only inhibited the VEGFR1 expression, but also inhibited non-cognate VEGF-A expression through interaction with miR-520a. Perturbation of FLT1P1 expression by RNA interference (RNAi) markedly inhibited tumor cell proliferation and xenograft tumor growth. This study identifies FLT1P1 antisense as a critical regulator of VEGFR1 and VEGF-A expression in CRC cells, and highlights its role in regulation of the pathogenesis of CRC. IMPLICATIONS: The VEGFR1 pseudogene, FLT1P1, is a novel and functional regulator of VEGF signaling and its targeting could be an alternative strategy to modulate its cognate/target gene expression and downstream activity in cancer.